Notes on Endoclita C. & R. Felder (Lepidoptera: Hepialidae) feeding on Eucalyptus in Vietnam, with new records and a new species - Pham, Duy Long; Chi, Nguyen Minh; Grehan, John R.; Khai, Tran Quang; Ignatev, Nikolai; Jones, Loren D.; Mielke, Carlos G.c.; Quang, Dao Ngoc; Yakovlev, Roman (Zootaxa, 2024)
A new species of Endoclita C. & R. Felder from Yen Lap district, Phu Tho province, Vietnam, E. phuthoensis sp. n. and the female of Endoclita coomani (Viette) are described as new to science. Both are recorded feeding on Eucalyptus plantations for the first time. Larval and pupal tunnels of E. phuthoensis sp. n. and E. coomani in host stems in Phu Tho and Lao Cai provinces, Vietnam are described and illustrated for the first time. Tunnels were found within one meter above the ground. They are initiated at the bark surface, extend into the stem, usually at a downward angle, then bend upwards for a distance of less than 24 cm, contrasting with the proximal (downward) orientation of the tunnel in E. vietnamensis Buchsbaum & Grehan and E. salvazi Tindale. The tunnel entrance is surrounded by callus tissue that larvae feed on under a web of silk and debris. At pupation, larvae first construct a silk membrane across the tunnel entrance. Endoclita marginenotatus (Leech, 1898) is recorded from Vietnam (Mt. Fansipan) for the first time from a single specimen collected within natural forest habitat.